Officer Buckle and Gloria - Rathmann, Peggy (New York : Putnam$1 (Bs,s, 1995)
The children at Napville Elementary School always ignore Officer Buckle$1 (Bs safety tips, until a police dog named Gloria accompanies him when he gives his safety speeches.s
Keywords: Safety -- Fiction; Police -- Fiction; Police dogs -- Fiction; Dogs -- Fiction; Schools -- Fiction